Healthcare professionals' satisfaction toward the use of district health information system and its associated factors in southwest Ethiopia: using the information system success model - Walle, Agmasie Damtew; Demsash, Addisalem Workie; Ferede, Tigist Andargie; Wubante, Sisay Maru (Frontiers in Digital Health, 2023)
Background: Ethiopia has the potential to use the district health information system, which is a building blocks of the health system. Thus, it needs to assess the performance level of the system by identifying the satisfaction of end users. There is little evidence about users’ satisfaction with using this system. As a result, this study was conducted to fill this gap by evaluating user satisfaction and associated factors of district health information system among healthcare providers in Ethiopia, using the information system success model. Methods: An institutional-based cross-sectional study was conducted from November to December 2022 in the Oromia region of southwest Ethiopia. A total of 391 health professionals participated in the study. The study participants were selected using a census. Using a self-administered questionnaire, data were collected. measurement and structural equation modeling analyses were used to evaluate the reliability, the validity of model fit, and test the relationship between the constructs, respectively, using AMOS V 26. Results: System quality had a positive direct effect on the respondent's system use (β = 0.18, P-value<0.001), and satisfaction (β = 0.44, P-value<0.001). Service quality had also a direct effect on the respondent's system use (β = 0.37, P-value<0.01), and satisfaction with using the district health information system (β = 0.36, P-value<0.01). Similarly, system use had also a direct effect on the respondent's satisfaction (β = 0.53, P-value<0.05). Moreover, Computer literacy had a direct effect on the respondent's system use (β = 0.63, P-value<0.05), and satisfaction (β = 0.51, P-value<0.01). Concussions: The overall user satisfaction with using the district health information system in Ethiopia was low. System quality, service quality, and computer literacy had a direct positive effect on system use and user satisfaction. In addition, system use and information quality had a direct positive effect on healthcare professionals ‘satisfaction with using the district health information system. The most important factor for enhancing system use and user satisfaction was computer literacy. Accordingly, for the specific user training required for the success of the district health information system in Ethiopia, the manager should offer additional basic computer courses for better use of the system.